2021
DOI: 10.1210/endocr/bqab168
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Receptor Expression in GABAergic Cells is Not Sufficient to Normalize Metabolism and Reproduction in Mice

Abstract: Previous studies indicate that leptin receptor (LepR) expression in GABAergic neurons is necessary for the biological effects of leptin. However, it is not clear whether LepR expression only in GABAergic neurons is sufficient to prevent the metabolic and neuroendocrine imbalances caused by LepR deficiency. In the present study, we produced mice that express the LepR exclusively in GABAergic cells (LepR VGAT mice) and compared them to wild-type (LepR +/+) and LepR-deficient (LepR Null/Null) mice. Although LepR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 77 publications
0
14
0
1
Order By: Relevance
“…Due to the fundamental role of reproduction for species survival, redundancy of neural pathways is expected, and developmental adaptations may have occurred in those studies. Of note, a recent study showed that re-expression of LepRb only in GABAergic cells is not sufficient for restoration of reproduction in otherwise LepRb null mice, emphasizing the need for other populations (Quaresma et al, 2021). Similarly, alternative metabolic signals may take over control in the absence of leptin signaling in this specific pathway (Hill et al, 2010; Hill and Elias, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the fundamental role of reproduction for species survival, redundancy of neural pathways is expected, and developmental adaptations may have occurred in those studies. Of note, a recent study showed that re-expression of LepRb only in GABAergic cells is not sufficient for restoration of reproduction in otherwise LepRb null mice, emphasizing the need for other populations (Quaresma et al, 2021). Similarly, alternative metabolic signals may take over control in the absence of leptin signaling in this specific pathway (Hill et al, 2010; Hill and Elias, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In‐house sensitive sandwich enzyme‐linked immunosorbent assays (ELISA) were adapted from published protocols to determine plasma LH (Brown et al, 2019; Quaresma et al, 2021) and FSH (De Paula et al, 2021; Ongaro et al, 2021) levels. A 96‐well high‐binding plate (9018, Corning) was coated with 50 μl of monoclonal mouse anti‐bovine LH beta subunit antibody (1:2500; Pablo Ross, UC Davis, 518B7; RRID: AB_2756886) or polyclonal guinea pig anti‐mouse FSH antibody (1:20,000; AFP1760191, NIDDK‐NHPP; RRID: AB_2665512) overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…In-house sensitive sandwich enzyme-linked immunosorbent assays (ELISA) were adapted from published protocols to determine plasma LH (Brown et al, 2019;Quaresma et al, 2021) for 2 h at room temperature (RT). The standard curve consisted of a twofold serial dilution of mouse recombinant LH (AFP-5306A, NIDDK-NHPP) or rat recombinant FSH (rFSH-RP-2, AFP4621B, NIDDK-NHPP) in 0.2% bovine serum albumin (BSA) PBS-T from 0.00976 to 5 ng/ml and 0.03125 to 16 ng/ml, respectively.…”
Section: Hormone Assessmentmentioning
confidence: 99%
“…Indeed, deleting Lepr selectively in GABAergic neurons ( Slc32a1 ( Vgat )‐Cre:: Lepr flox/flox ) was shown to increase food intake and body weight close to the phenotype of global Lepr KO mice (Vong et al, 2011). Based on these results, a recent study took a complementary approach to determine whether Lepr re‐expression only in GABAergic neurons ( Slc32a1 ‐Cre:: Lepr TB/TB ) was sufficient to normalize the severe obesity phenotype of global Lepr KO mice (Quaresma et al, 2021). Lepr expression exclusively in GABAergic cells induced a drastic reduction in body weight and fat mass compared to mice globally deficient for Lepr‐b ( Lepr TB/TB ) but could not quite normalize these parameters to control levels.…”
Section: The Main Direct Effects Of Leptin On Energy Balance Involve ...mentioning
confidence: 99%
“…In fact, Lepr expression in GABAergic neurons was sufficient to completely normalize food intake, but only partially restored the reduced oxygen consumption of Lepr TB/TB mice. Plasma leptin, insulin, and glucose levels were also not completely rescued (Quaresma et al, 2021). This partial recovery suggests the involvement of many neuronal populations mediating specific effects of leptin, rather than one leptin‐responsive neuronal population mediating all of leptin's effects.…”
Section: The Main Direct Effects Of Leptin On Energy Balance Involve ...mentioning
confidence: 99%